Diagnosis and management of eosinophilic otitis media: a systematic review. (1st June 2021) - Chen, Tiffany; Ashman, Peter E.; Bojrab, Dennis I.; Johnson, Andrew P.; Hong, Robert S.; Benson, Brian; Svider, Peter F.
Abstract: Background: Eosinophilic Otitis Media (EOM) is a relatively newly defined entity of recurrent and resistant otitis media. Objective: To perform a systematic review of otologic manifestations, diagnosis and management of eosinophilic otitis media (EOM). Methods: 393 patients diagnosed with EOM of 26 studies met inclusion criteria and were assessed for demographics, otologic manifestations, diagnostic criteria fulfilled, and medical and surgical treatments. Results: Most common otologic manifestations were hearing loss (65%), otitis media with effusion (16%), tympanic membrane perforation (13%), and otorrhea (13%). 93% had a predominantly eosinophilic middle ear effusion, 95% had asthma, 85% had a highly viscous middle ear effusion, 71% had nasal polyposis, and 58% had resistance to conventional treatment. For treatment, 39% received intratympanic steroid injections, 33% received systemic steroids, 17% received steroid ear drops and 13% received a biological agent. 39% of patients underwent a surgical intervention with 26% receiving functional endoscopic sinus surgery and 18% receiving myringotomy with tube insertion. Success rates were highest with use of intratympanic steroids (45%), systemic steroids (26%), and biological agents (58%). Conclusion: Intratympanic steroids show the most efficacy in treating EOM, and aggressive optimization of asthma may be beneficial in resolving otologic symptoms. Surgery should be reserved for refractory cases and complications.